Coupled damage and plasticity models derived from energy and dissipation potentials - Einav, I; Houlsby, G; Nguyen, G (2007)
A theoretical framework is defined that allows plasticity and damage models of inelastic behaviour to be combined within a consistent approach. Much emphasis is placed on the fact that, within this framework, the entire constitutive response is specified through two potential functions, with no additional assumptions or evolution equations being necessary. Both plastic strain and damage parameter have roles as internal variables within the theory. Two classes of models are derived: involving respectively uncoupled and coupled plasticity and damage. Examples of application of the theory are presented. Crown Copyright © 2006.